INFORMATION LITERACY UNTUK PEMBELAJARAN DI PENDIDIK.AN TINGI - Dina Utami (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Information af.re is marked with the abundant of information. It isopportunities and challenge as well. Jn higher education, studentsdeal with this information in their everyday live. Informationliteracy gives students the ability to retrieve, evaluate,communicate, and used the information available out thereeffectively. Information literacy gives great contribution to createlife long learners. Considering it 's importance, higher educationshould equipped their students with information literacy,incorporated in it 's curriculum and pedagogy.